Peran Inovasi Pendidikan pada Pembelajaran Berbasis Digital - Hamidah D; Diya Andini; Ledy Sukma; Lukita Triandini (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This research aims to develop educational innovations and the use of technology that can create conducive learning conditions because it can facilitate and accelerate students' work, as well as improve students' skills in utilizing technological advances. This research is a literature study with a type of descriptive qualitative research method with a literature review that seeks to describe the role of educational innovation in digital technology-based learning. In this study, the author uses various written sources such as articles, journals, and documents that are relevant to the study in this study. This literature study focuses on the role of educational innovation, digital technology in education, and the use of technology in education. The results of the study show that innovation is a process of renewal and change. The world of education needs innovation to continue to develop and be able to keep up with the development of other fields. The use of technology has a positive and negative impact. The impact can be focused on the positive and minimize the negative impact if there is good cooperation from various parties so that the use of technology is in accordance with its purpose. The role of educational innovation in digital technology-based learning is very important. Innovation is needed so that the use of digital technology can be carried out optimally and comprehensively. It is hoped that all elements of society can support and collaborate to optimize various educational innovations based on digital technology. The presence of technology today, it is hoped that it can be used well by all parties such as teachers and other education actors.